INFLUENCE OF PROACTIVE PERSONALITY ON JOB PERFORMANCE OF BANK EMPLOYEES IN PAKISTAN: WORK ENGAGEMENT AS A MEDIATOR - Munazza Zahra; Daisy Mui Hung Kee (International Journal of Management Studies, 2021)
The purpose of this study was to determine whether the proactive personality of Pakistani bank employees influenced their job performance. With the awareness of the importance of job performance in the banking sector of Pakistan, researchers also examined the mediating role of work engagement in the relationship between proactive personality and job performance. A total of 315 responses were obtained from officers to test the relationship between proactive personality and job performance, and to examine the mechanism via work engagement. The researchers analyzed respondents’ demographic profiles in SPSS version 23 and developed several hypotheses through structural equation modelling technique which were tested in SmartPLS version 3. The findings of the study showed a significant positive relationship between proactive personality and the three dimensions of job performance: task performance, individual- directed citizenship behavior (OCBI), and organizational-directed citizenship behavior (OCBO). The study results also supported the main hypothesis that work engagement mediated the relationship between proactive personality and job performance. The findings of the study present a few useful insights to the HR department and policymakers in the banking sector. Proactive personality should be considered as one of the necessary dispositions to be evaluated in hiring decisions. Bank management should devote more attention on the work engagement of employees and its related factors to boost employees’ performance at work.